2007
DOI: 10.1007/s10552-007-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the anatomic distribution of cutaneous melanoma in two populations with different levels of sunlight: the west of Scotland and Queensland, Australia 1982–2001

Abstract: To explore whether the anatomic distribution of melanoma differs with ambient sunlight levels, we compared age- and site-specific melanoma incidence in two genetically similar populations from different geographic regions. We ascertained all new cases of invasive cutaneous melanoma in the west of Scotland and Queensland 1982-2001. Melanoma incidence was calculated for four anatomic regions (head and neck, trunk, upper and lower limbs), standardized to the European population and adjusted for relative surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
5
17
0
1
Order By: Relevance
“…This too might be expected, at least for the head and neck, because of the head and neck’s generally greater exposure to the sun and greater risk of melanoma per unit of surface area than other body sites, particularly in older people. 44, 45 This possible association of multiple melanomas with higher sun exposure is supported by the stronger association of solar elastosis with first melanomas than single melanomas in the present study, observed associations of high sun exposure 44 and lack of sunscreen use 4 with an increased risk of multiple melanomas, and the finding that solar exposure at any age was associated with increased risk of developing multiple primary melanomas in the GEM study. 46 …”
Section: Discussionsupporting
confidence: 78%
“…This too might be expected, at least for the head and neck, because of the head and neck’s generally greater exposure to the sun and greater risk of melanoma per unit of surface area than other body sites, particularly in older people. 44, 45 This possible association of multiple melanomas with higher sun exposure is supported by the stronger association of solar elastosis with first melanomas than single melanomas in the present study, observed associations of high sun exposure 44 and lack of sunscreen use 4 with an increased risk of multiple melanomas, and the finding that solar exposure at any age was associated with increased risk of developing multiple primary melanomas in the GEM study. 46 …”
Section: Discussionsupporting
confidence: 78%
“…The results are however in line with international research assessing anatomic distributions and gender profiles of melanoma (e.g. [42]) and naevi (e.g. [38]), found to be largely similar between populations residing at different latitudes [43].…”
Section: Discussionsupporting
confidence: 89%
“…In men, the highest incidence rates are observed on the trunk overall [4], but after surface area adjustment, the highest rates are seen on the trunk of only younger men (under 40 years), but in older men they are seen on the head and neck [5][6][7]. In women, the highest incidence rates are observed on the trunk and limbs [4][5][6][7].…”
Section: Introductionmentioning
confidence: 97%
“…Altogether the limbs comprise 60% of the total skin surface area. Even after adjustment for surface area, the lower limbs show surprisingly high incidence rates of melanoma, especially in women living in temperate climates such as in Canada, New Zealand and Scotland [6,12], whereas women of similar ancestry living in sunny climates show highest incidence rates of melanoma per unit of skin on the upper followed by the lower limbs [7].…”
Section: Introductionmentioning
confidence: 99%